Effect of Subcutaneous Tissue on Changes in Thigh Circumference Following Anterior Cruciate Ligament Reconstruction - Yoshii, Ryo; Konishi, Yu; Ando, Daisuke; Ochiai, Satoshi; Hagino, Tetsuo; Dobashi, Shohei (International Journal of Sports Medicine, 2019)
Circumference measurements have been used to estimate muscle cross-sectional area (CSA) in clinical settings. Measurements of thigh circumference are affected by muscle and subcutaneous fat (SF). In fact, SF could increase over a short period. Therefore, clarifying the relationship between thigh circumference and muscle and SF following ACL reconstruction is important. This study’s primary purpose was to examine pre- and post-operative changes in thigh circumference, thigh muscles and SF CSAs in both legs. Secondary, the relationship between thigh circumference and muscle and SF CSAs was examined to demonstrate that circumference measurements could be used to detect atrophy. Quadriceps, hamstrings, and SF CSAs at 15, 10, and 5 cm proximal to the patella were measured by MRI pre- and 4 weeks postoperatively to examine how reconstruction affected those tissues in the thighs. The results showed increases in SF CSA (r=0.72 at 10 cm, r=0.67 at 15 cm) greatly affected thigh circumference in females on the surgical side. In males, increases in SF CSA (r=0.83) at 15- and 5-cm and decreases in quadriceps muscle CSA (r=0.73) at 5 cm affected thigh circumference on the surgical side. Thigh circumference measurements might not reflect actual muscle CSA in ACL patients.
Keywords: ACL reconstruction; thigh circumference; fat; MRI